ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTsN 3 KUANTAN SINGINGI - Riza Derniati; Yenita Roza; Maimunah Maimunah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
The need for mathematical problem solving has an important role in learning Mathematics, so the ability is needed. Based on that research is conducted which aims to analyze the problem solving of students of MTsN 3 Kuantan Singingi on the material making flat side space. The method used in this research is descriptive qualitative method. The research subjects consisted of 8 students divided into high, medium and low abilities selected from 20 students, class VIII1 MTsN 3 Kuantan Singingi in 2019/2020. The method used is a test and interview. The overall results of the study are 41% obtained from indicators that solve problems, 75% for indicators approved by the strategy, 58% for indicators that solve problems and 22% to obtain indicators that are readmitted. While the problem of mathematical problem solving ability found is not suitable with the concept of getting the right space and calculation plan to use.